Academic units in a complex, changing world adaptation and resistance - De Zilwa, Deanna (Springer, 2010)
This book uses case studies of academic units from Australian public universities to explore the reasons why those units respond in different ways to similar contemporary challenges. The 'academic units' - departments, schools and faculties - in the world's public universities may be their own administrative fiefdoms, but the wider environment within which they operate is both complex and dynamic. In fact, today's academic landscape is barely recognizable from what it was like two decades ago. The globalization of higher education markets for students, faculty and research funding has expanded.